ANALISIS PENGARUH PERKEMBANGAN PENDAPATAN PERUSAHAAN, TOTAL ASET, DAN TOTAL TINGKAT UPAH TERHADAP JUMLAH TENAGA KERJA PERUSAHAAN - Tain, Anas; Bakhtiar, Ary; Wulandari, Ratu Cahyaningrum (Jurnal AGRISEP, 2020)
The research has a purpose as follows, analyzing the impact between the total income of agricultural sector companies with total national income. Analyzing the impact of total income, total assets, and total wage level to the labour of agricultural sector companies. Analyzing the frequently relation between the amount of labour in agricultural sector companies with total national income. National income with company income does not have a relation but, there is a significant impact. The results of the analysis of the impact of developments on the amount of labor in agricultural sub-sector companies are the total asset variables that have a significant impact. while company income and total wage level variables do not significantly influence the number of workers. The results of the analysis of the influence of the development of state revenue and the number of labour back and forth have a significant effect. Whereas the company income variables and total wage level not significantly influence the amount of labour. The results of the analysis development national income and the amount of labour frequently have a significant impact.